Effect of Nylon Membrane Thickness on the Value of Sound Transmission Loss as an Alternative Insulation Material - Wenny Maulina; Totok Wicaksono; Agung Tjahjo Nugroho (Lambung Mangkurat University Press, 2023)
Measurements of sound transmission loss have been successfully carried out on various thicknesses of nylon membrane as an absorbing material. Nylon membrane were prepared using hydrogen chloride (HCl) and acetyl aceton in the casting solution by phase inversion methods. Nylon membrane with different thickness used in this reseach were 1 mm, 2 mm, 3 mm, 4 mm, and 5 mm. Measurement of sound transmission loss was carried out using a reverberation chamber with sound frequencies of 125 Hz, 250 Hz, 500 Hz, 1000 Hz, 2000 Hz, 4000 Hz. The results show that, with the increase of thickness of nylon membrane, sound transmission loss of nylon membran was improved. The sound transmission loss of nylon membrane with thickness of 4 mm is the best, whose sound trasnmission loss was up to 46.39 dB at 4000 Hz. This nylon membrane is suitable for lightweight sound barriers and is promising and worthy of further study.